MODEL PEMBERDAYAAN-PARTISIPATIF MASYARAKAT MELALUI KELOMPOK TANI - Hayat, Sahidin; Saifudin, M; Jauhari, Tontowi (Agros Journal of Agriculture Science, 2024)
Empowerment is an effort to improve the welfare of disadvantaged communities, aligning with the goals of Sharia economics. Community involvement is integral to this process. This research aims to provide a general overview of the importance of community involvement in the empowerment process. This research is a literature study whose data source comes from articles with the keyword "Community Participatory Empowerment". This research was taken from open knowledge maps. Selected articles were published in 2020-2024. The research results show that community involvement is very important to make empowerment easier, participatory communication with the community can make it easier to take policies without creating friction with the community, and the government's role in the empowerment process is important either as a regulator, dynamizer, or facilitator.